Empowering Cadres of Integrated Health Posts and Family Welfare Programs in Implementing Child Protection Based on Law No. 35 of 2014 - Sofian Syaiful Rizal; Wildanul Ulum (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
This community service program aims to enhance the capacity of Integrated Health Post and Family Welfare Program cadres in understanding and concretely implementing Law Number 35 of 2014 concerning Child Protection at the village level. The program adopted a participatory and community-based approach through field observations, focus group discussions (FGDs), interactive legal training, and simulations of child violence case handling. The results indicate a significant improvement in the cadres’ understanding of various forms of child abuse, children's legal rights, and appropriate reporting mechanisms. Furthermore, the program succeeded in establishing a joint commitment to create a community-based child violence reporting system and fostered collaborative networks with child protection institutions at the district level. The impact of this initiative is evident in the increased legal awareness, the active participation of cadres as child protection agents, and the tangible support from the village government to prioritize child protection in future policy planning. This program is expected to serve as a replicable model for other villages in building a sustainable, community-based child protection system.